Association between physical activity and cardiovascular risk factors in individuals undergoing cardiac rehabilitation program - Bernardo, Aline Fernanda Barbosa [UNESP]; Rossi, Renata Claudino [UNESP]; de Souza, Naiara Maria [UNESP]; Pastre, Carlos Marcelo [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP] (FapUNIFESP (SciELO), 2013)
Introduction: Physical activity (PA) practice presents an inverse relation with risk factors (RF) of cardiovascular disease, with positive effects in quality of life and other physical and psychological variables. However, the benefits of daily activities have not been established. Objective: To investigate the prevalence and association of cardiovascular risk factors and physical activity in different categories of patients under a cardiac rehabilitation program. Methods: 69 participants of a cardiac rehabilitation program were evaluated and weight, height and blood pressure were checked. Afterwards, the patients answered questionnaires to assess self-reported physical activity level, stress level and verify the presence of RF. Logistic regression was used to estimate odds ratio. Results: High prevalence of RF was found in the subjects, age and hypertension were more prevalent while smoking and stress had lower prevalence. Most individuals were classified as sedentary, except for locomotion PA (LPA). Conclusion: That there is high prevalence of RF in patients attending cardiac rehabilitation programs, while sedentary ones are more likely to have the RF hypertension, obesity, smoking, alcohol and stress than the active ones, depending on the PA category.
Keywords: Motor activity; Rehabilitation; Risk factors